The Accuracy of Subsidised Fertiliser Distribution Based on the 6t Principle Among Paddy Field Farmers (A Case Study of Harau District, Lima Puluh Kota Regency, West Sumatra) - Nila Sari; Andrik Marta; Syinthia Ona Gusrike Afner (Citakonsultindo, 2026)
This study analyzes the accuracy of the distribution of subsidized fertilizers based on the 6 Right principle (6T), namely the right type, the right quantity, the right price, the right time, the right place, and the right target group. The study was conducted in 2025 using a survey. The research location was deliberately chosen because it is one of the areas with high use of subsidized fertilizers. The respondents were 65 farmers who received subsidized fertilizers. The research data consisted of primary data obtained through interviews using a structured questionnaire and secondary data from the agricultural service, farmers' organizations, official sales outlets, and relevant literature. The data analysis was performed descriptively and quantitatively. The results of the study demonstrate that the distribution mechanism of subsidized fertilizers in the Harau district has been implemented through the phases of RDKK preparation, verification of farmer data, distribution by official distributors, and distribution via official sales outlets. In general, the implementation of the Six Rights Principle is proceeding quite well, particularly regarding the right type and the right place. However, various obstacles remain, such as delays in the distribution of fertilizer, limited allocation relative to farmers' needs, and inconsistencies in data regarding grant recipients.